Manajemen Akselerasi Mutu Sekolah Dasar: Penelitian Tindakan Kelembagaan - Ibrahim Bafadal (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This action research was designed to describe the management strategies implemented to accelerate the quality of elementary school. This three-year study applied a cycle model of Kemmis and McTaggart, and was held in SD Islam Sabilillah, Malang. The results revealed that the quality management consisted of establishing school vision, self assessment, identifying the need for development, formulating the goal of development, designing the development program, implementing the program, and evaluation. The strategic efforts in accelerating the quality were a quality-oriented program, independence of human-resource, participation of stakeholders, and transparency in financial management.